Rethinking pain communication of patients with Alzheimer’s disease through E-textile interaction design - Li, Yanheng; Bai, Long; Mao, Yaxuan; Ren, Hongliang; Qiao, Yu; Tong, Xin; Lc, Ray (Frontiers in Physiology, 2023)
Older individuals are easily prone to chronic pain. Due to the complexity of chronic pain, most elderly often have difficulty expressing pain to others to seek assistance, especially those with Alzheimer's disease (AD). The caregivers cannot instantly discover the patients' pain condition and provide timely pain management. This project applies physiological signal sensing technology to help AD patients express the presence of pain non-verbally. We embed sensors on patients' handkerchiefs to identify the patient's abnormal physical activity when pain occurs. Next, we translate the physiological signal into qualitative pain occuration information to send to caregivers.Then, utilizing multi-sensory stimulation intervention, we create an electronic textile (e-textile) tool to help caregivers effectively support patients in pain. Pain perception can be independent of subjective expressions and tangibly perceived by others through our textile prototype. The e-textile handkerchiefs also bring up a new guide to facilitate communication for caregivers when their patients are in pain. Our e-textile system may contribute to pain detection and management bio-sensing tool design for special elderly groups, especially those with weakened cognition and communication abilities. We provide a new approach to dealing with the pain of AD patients for healthcare professionals.